The Influence of Workload, Work Environment, and Organizational Communication on Employee Performance at the North Sumatra Provincial Manpower Office - Kartika Sari Lubis; Ardila Dwi Sahara (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Objective – To analyze the effect of workload, work environment, and organizational communication on employee performance at the North Sumatra Provincial Manpower Office. Methods/approach – Associative quantitative design; census of 77 employees with saturated sampling; primary data from structured questionnaires and secondary data from agency documents; multiple linear regression analysis. Findings – (1) Workload has a positive and significant partial effect on performance; (2) work environment has no significant effect; (3) organizational communication has no significant effect; and (4) all three simultaneously have a positive and significant effect. Novelty/value – (i) Integration of POAC and HRM theories (Dessler); (ii) the context of local government bureaucracy with the complexity of public services; (iii) a broader range of respondents (77 civil servants) enriched by pre-surveys and interviews with the Head of the Human Resources Division; and (iv) a comprehensive simultaneous model that tests the three variables in a single regression to explain performance.